2017
DOI: 10.3727/096504016x14817158982636
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DDX5 Inhibits the Proliferation and Tumorigenesis in Esophageal Cancer

Abstract: DEAD (Asp-Glu-Ala-Asp) box protein 5 (DDX5), a prototypical member of the DEAD/H-box protein family, has been involved in several human malignancies. However, the expression and biological role of DDX5 in esophageal cancer (EC) remain largely unknown. In this study, we examined the role of DDX5 in regulating EC cell proliferation and tumorigenesis and explored its possible molecular mechanism. We found that DDX5 was overexpressed in human EC cell lines. In addition, knockdown of DDX5 significantly inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Previous studies have suggested an important role for DDX5 in regulating transcription in conjunction with multiple, sequence-specific transcription factors [21]. DDX5 is implicated in cancer development and progression by regulating cell proliferation, migration, cytoskeletal reorganization, and EMT [22][23][24][25][26]. DDX5 has been found to be involved in the oncogenic processes of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested an important role for DDX5 in regulating transcription in conjunction with multiple, sequence-specific transcription factors [21]. DDX5 is implicated in cancer development and progression by regulating cell proliferation, migration, cytoskeletal reorganization, and EMT [22][23][24][25][26]. DDX5 has been found to be involved in the oncogenic processes of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation and overexpression of DDX5 are found in human cancers, and its overexpression predicts advanced clinical stage and poor survival in colorectal cancer (CRC) patients (25,26,27). Knockdown of DDX5 inhibited the proliferation of cancer cells in vitro and the growth of xenografts in immunodeficient hosts (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, we proved that miR-1275 affected EC radiosensitivity by targeting WNT1-activated Wnt/β-catenin pathway, and similar mechanism was previously unearthed in the influence of miR-301a on the migration and radiosensitivity of EC cells. 43 More importantly, the rescue of WNT1 on miR-1275-regulated EC radiosensitivity was mediated by the enhancement of WNT1-regulated Wnt/β-catenin signalling per se on EMT, 44,45 thus indicating the strong association among miR-1275, EMT and WNT1 in regulating the radiosensitization of EC cells.…”
Section: Discussionmentioning
confidence: 96%